Review of Impact of 2004 Great Sumatra-Andaman Mega Thrust Earthquake and Tsunami on Affected Countries using ECLAC DaLA Framework - Imtiyaz Akbar, Najar; Raudhah, Ahmadi; Nadeem Akbar, Najar; Shahana, Akbar; Nurul Syafiqah, Hanapi (MAT Journals, 2020)
This study carries the effects of the great Sumatra-Andaman earthquake on the neighboring countries. on Sunday, 26 December 2004 at 00:58:53. UTC the Earthquake struck the Sumatra-Andaman island, which disrupted the Sunda Trench Subduction zone, the undersea mega-thrust earthquake was caused due to the subduction of Indo-Australian plate below the Eurasian plate. The epicenter of this earthquake was located 160 Km of the Western coast of North Sumatra Indonesia with a depth of 30 Km prompted a devastating tsunami. After the global monitoring in the 1980s, it was the third major devastating earthquake with the seismic moment of Mo = 1:00 X 1023 to 1:15 X 1023 Nm and the corresponding magnitude of 9.0-9.3 on Richter scale and had the longest interval of time of faulting ever detected between 8.3 to 10 minutes. The propagation of rupture was found from South to North and the southerly part of the fault ruptured at a speed of 1.739 miles/s. The objective of this review paper is to study the consequences of the 2004 great Sumatra-Andaman earthquake on Sumatra Island and its surrounding countries using an accounting framework for damage and loss assessment that is ECLAC DaLA methodology.